Who could be One Health Activist at the community level?: A case for India - Sandul Yasobant; Walter Bruchhausen; Deepak Saxena; Farjana Zakir Memon; Timo Falkenberg (BMC, 2021)
Abstract Background Community health workers (CHWs) are the mainstay of the public health system, serving for decades in low-resource countries. Their multi-dimensional work in various health care services, including the prevention of communicable diseases and health promotion of non-communicable diseases, makes CHWs, the frontline workers in their respective communities in India. As India is heading towards the development of One Health (OH), this study attempted to provide an insight into potential OH activists (OHA) at the community level. Thus, this case study in one of India's western cities, Ahmedabad, targeted identifying OHA by exploring the feasibility and the motivation of CHWs in a local setting. Methods This case study explores two major CHWs, i.e., female (Accredited Social Health Activists/ASHA) health workers (FHWs) and male (multipurpose) health workers (MHWs), on their experience and motivation for becoming an OHA. The data were collected between September 2018 and August 2019 through a mixed design, i.e., quantitative data (cross-sectional structured questionnaire) followed by qualitative data (focus group discussion with a semi-structured interview guide). Results The motivation of the CHWs for liaisoning as OHA was found to be low; however, the FHWs have a higher mean motivation score [40 (36-43)] as compared to MHWs [37 (35-40)] out of a maximum score of 92. Although most CHWs have received zoonoses training or contributed to zoonoses prevention campaigns, their awareness level was found to be different among male and female health workers. Comparing the female and male health workers to act as OHA, higher motivational score, multidisciplinary collaborative work experience, and way for incentive generation documented among the female health workers. Conclusion ASHAs were willing to accept the additional new liaison role of OHAs if measures like financial incentives and improved recognition are provided. Although this study documented various systemic factors at the individual, community, and health system level, which might, directly and indirectly, impact the acceptance level to act as OHA, they need to be accounted for in the policy regime.